Knowledge, attitudes, and practices regarding preconception or early pregnancy single-gene genetic disease screening among reproductive-aged individuals - Yinghui Ren; Zhiling Wu; Xueyan Wang; Qun Sun (BMC Public Health)
Abstract Background This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding preconception or early pregnancy single-gene genetic disease screening among individuals in early pregnancy or preparing for pregnancy. Methods A cross-sectional survey was conducted from April 1, 2024, to June 30, 2024, using a validated, self-designed questionnaire which was distributed online to collect data on participants’ demographic information and KAP scores. Results A total of 562 valid questionnaires were obtained, with 397 (70.64%) female participants. The median (IQR) scores for knowledge, attitude, and practice were 17 (7, 29) (possible range: 0–42), 40 (35, 44) (possible range: 11–55), and 30 (19, 36) (possible range: 9–45), respectively. The mediation analysis based on path analysis model demonstrated that the number of children (β = 0.178, p = 0.005), screening experience (β = -0.288, p = 0.001), gender (β = -0.162, p = 0.016), and binge drinking (β = 0.150, p = 0.006) directly influenced knowledge. Additionally, knowledge (β = -0.224, p = 0.013), occupation (β = 0.119, p = 0.015), education (β = 0.181, p = 0.015), gender (β = 0.182, p = 0.004), and binge drinking (β = -0.158, p = 0.011) directly affected attitude. Practice was directly influenced by knowledge (β = -0.163, p = 0.007), attitude (β = 0.609, p = 0.009), number of premature births (β = 0.087, p = 0.006), and number of abortions (β = 0.114, p = 0.013). Gender (β = 0.036, p = 0.010) and binge drinking (β = -0.034, p = 0.005) indirectly affected attitude, while knowledge (β = -0.136, p = 0.011) indirectly influenced practice. Conclusions Individuals either in early pregnancy or preparing for pregnancy in our study population demonstrated variable levels of knowledge, generally positive attitudes, and moderate practices towards preconception and early pregnancy single-gene genetic disease screening. Targeted educational interventions should be implemented to enhance knowledge and improve screening practices, particularly focusing on groups with lower knowledge scores, such as those with less screening experience or specific demographic characteristics. Clinical trial registry number Not applicable.